The Efficacy of Aquatic Therapy for Pain in Knee Osteoarthritis: A Systematic Review and Meta-Analysis - Rachmat, Ahdiyat Ananta; Wahyuni, Wahyuni (Indonesian Journal of Medicine, 2022)
Background: Osteoarthritis (OA) is a joint disease that affects adults to the elderly in which the incidence and prevalence of OA will increase with age. One of the interventions to reduce pain for improving the quality of life in patients with knee osteoarthritis is by providing aquatic therapy. This study aims to determine the effectiveness of aquatic therapy for pain in patients with knee osteoarthritis.Subjects and Method: It was a metaanalysis study using PICO. P: patients with knee osteoarthritis. I: aquatic therapy. C: nonaquatic therapy. O: reduced pain. The articles used in this study were obtained from several databases namely Google Scholar, PubMed, NCBI, Science Direct, and Springer Link. The keywords used were "osteoarthritis knee" OR "OA knee" AND "aquatic" OR "aquatic physiotherapy" OR "aquatic therapy" OR "aquatic exercise" OR "hydrotherapy" AND "quality of life" OR "QOL" AND "pain" and "RCT" or "randomized control trial". The article included in this study was a fulltext article with a Randomized Controlled Trial study design. The Review Manager 5.3 application was used to analyze articles. Results from the metaanalysis were reported using the PRISMA flow diagram.Results: A total of 9 articles that had been analyzed were from Spain, Thailand, Brazil, Australia, New Zealand, Korea, and Italy. Studies show that elderly with knee osteoarthritis who obtained aquatic therapy experienced lower pain by 0.62 units than those who did not obtain aquatic therapy thus improving the quality of life, and this effect was claimed to be statistically significant (SMD = 0.62; CI 95% 1.13 to 0.11; p <0.001).Conclusion: Aquatic therapy reduces pain and has an impact on improving quality of life.Keywords: aquatic therapy, knee osteoarthritis, pain, quality of life.Correspondence: Ahdiyat Ananta Rachmat, Study Program of Physiotherapy, Faculty of Health Science, Universitas Muhammadiyah Surakarta. Jl. A. Yani, Mendungan, Pabelan, Kartasura, Sukoharjo Regency, Central Java 57169, Indonesia. Email: ahdytannta@gmail.com. Phone: 082255733709.Indonesian Journal of Medicine (2022), 07(04): 428-438https://doi.org/10.26911/theijmed.2022.07.04.08